An Interdecadal Increase in the Spring Bering Sea Ice Cover in 2007 - Wu, Renguang; Chen, Zhang (Frontiers in Earth Science, 2016)
The sea ice coverage of the Northern Hemisphere as a whole has been declining since 1979. On contrary, the March-April sea ice concentration in the Bering Sea experienced a prominent increase in year 2007. The present study documents the changes in surface air temperature, surface heat fluxes, sea surface temperature, and atmospheric circulation accompanying the above interdecadal change in the Bering Sea ice concentration. It is shown that an obvious decrease in surface air temperature, sea surface temperature, and surface net shortwave radiation occurred in concurrent with the sea ice increase. The surface air temperature decrease is associated with a large-scale circulation change, featuring a decrease in sea level pressure extending from the Pacific coast of Alaska to northwestern Europe and an increase in sea level pressure over the high-latitude Asia and the high-latitude North Atlantic Ocean. The enhancement of northwesterly winds over the Bering Sea led to a large decrease in surface air temperature there. The associated increase in upward turbulent heat flux cooled the sea surface temperature in the waters south of the ice covered region, favoring the southward expansion of ice extent. This, together with a positive ice-albedo feedback, amplified the sea ice anomalies after they were initiated, leading to the interdecadal increase in sea ice in the Bering Sea.